Chirality and Excited State Proton Transfer: From Sensing to Asymmetric Synthesis. Issue 8 (26th June 2019) - Posey, Victoria; Hanson, Kenneth
Abstract: Excited state proton transfer (ESPT) is a unique photochemical process where the electron density shift of a molecule in the excited state dramatically decreases the p K a  value of a proton donor site. A majority of ESPT research to date has focused on achiral molecules but there is growing interest in understanding/harnessing ESPT to/from chiral molecules. This review summarizes and critically examines the literature to date describing the role of ESPT in enantioselective fluorescence sensing, asymmetric synthetic organic chemistry, and photoisomerization of chiral molecules. Our goal is to show that despite ESPT of chiral molecules being a relatively new pursuit, there has been significant progress and even greater potential for ESPT in these and other applications yet to be realized. Abstract : Excitement about proton transfer ! In the excited state, many chiral molecules can undergo excited state proton transfer (ESPT) which enables access to unique intermediates and reactivities. In this Review, we provide a comprehensive look at the literature describing ESPT to/from chiral molecules and their application in enantioselective fluorescence sensing, asymmetric synthetic organic chemistry, and photoisomerization